Tribocorrosion behaviour of bio-functionalized porous Ti surfaces obtained by two-step anodic treatment. (15th April 2020) - Costa, A.I.; Sousa, L.; Alves, A.C.; Toptan, F.
Graphical abstract: Highlights: Hierarchical porous structure with tailored chemical composition was obtained by a facile two-step anodic treatment. Hierarchical surfaces presented improved wettability, corrosion and tribocorrosion resistance. Wear-corrosion mechanisms involved in each bio-functionalization step is discussed. Abstract: A bio-functionalized porous surface was obtained on Ti by a two-step anodic treatment and its corrosion and tribocorrosion behaviour were evaluated. The first-step provided macro-porosity while the second-step, a bio-functionalization process by micro-arc oxidation (MAO), provided an oxide layer (anatase + rutile) with micro-pores and bio-active elements (Ca + P). Corrosion and tribocorrosion behaviour were improved due to the protective role given by the oxide layer formed on the second-step. Tribocorrosion mechanisms for the bio-functionalized porous structures are presented.